2020
DOI: 10.1088/1742-6596/1569/3/032041
|View full text |Cite
|
Sign up to set email alerts
|

Field-based Analyses on Approach Temperatures for Performance Evaluation of Centralized Air Conditioning System in a Shopping Mall Building

Abstract: This paper presents field analyses on the influences of condenser and evaporator approach temperatures of water cooled air conditioning system for a shopping mall. The mall building comprises food and non-food retail stores and uses a centralized air conditioning (AC) system to condition the entire building. The AC system comprises three chillers with the same cooling capacity. Chillers’ performance parameters included power consumption, condensing and evaporating temperatures, evaporator-condenser approach te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…Higher evaporating temperature can increase refrigeration capacity; lower power consumption and improve compressor efficiency as it has been found and proven in this study. Additionally, the results are also in agreement with [24][25][26] who have reported that capacity and cooling efficiency of a refrigeration system decreases with higher condensing temperature and lower evaporating temperature.…”
Section: Energy Performance Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Higher evaporating temperature can increase refrigeration capacity; lower power consumption and improve compressor efficiency as it has been found and proven in this study. Additionally, the results are also in agreement with [24][25][26] who have reported that capacity and cooling efficiency of a refrigeration system decreases with higher condensing temperature and lower evaporating temperature.…”
Section: Energy Performance Analysissupporting
confidence: 91%
“…Furthermore, transmission losses can be reduced by replacing large compressors with smaller compressors closer to the end user. The capacity and cooling efficiency of the system decreases with higher condensing temperature and lower evaporation temperature [24][25][26]. Lower system performance is associated with increased irreversibility during compression, and higher compressor discharge temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Di antara utilitas bangunan, peningkatan penggunaan energi sistem pemanas, ventilasi, dan AC atau lebih dikenal dengan HVAC menjadi sangat signifikan [11]. Beberapa solusi telah diusulkan untuk mempromosikan konservasi energi seperti pengembangan sistem AC yang dilengkapi dengan sistem heat recovery untuk memanaskan air [12][13][14][15][16]; menjaga kinerja sistem melalui pemantauan ketat pada parameter kunci chiller termasuk temperatur approach evaporator dan kondensor [17]; dan mengoptimalkan distribusi sistem sirkulasi air dingin [18]. Hal ini dapat mendorong penerapan efisiensi energi yang lebih luas, untuk mendukung komitmen Pemerintah Indonesia dalam mengurangi emisi Gas Rumah Kaca (GRK) sebesar 26% pada tahun 2020 [19].…”
Section: Pendahuluanunclassified